2017
DOI: 10.5483/bmbrep.2017.50.12.096
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin expression is upregulated by PI-3K/Akt activation in tamoxifen-resistant breast cancer cells

Abstract: Fibronectin (FN) plays important roles in the EMT in a variety of cancer cell types. However, the mechanism by which FN expression is regulated in tamoxifen-resistant (TamR) breast cancer cells has not yet been fully elucidated. Aberrant FN expression was associated with poor prognosis in patients with luminal type A breast cancer. In addition, FN was upregulated in TamR cells. To investigate the mechanism by which FN expression is regulated, we assessed the levels of phosphorylated Akt, JNK, and STAT3 and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Another recent study indicated that the dysregulated of FN1 restricted prostate cancer cell invasion [12]. And the enhanced fibronectin expression in tamoxifen-resistant breast cancer cells had been reported by You et al [13]. However, the biological function of FN1 in RAIresistant PTC has few been reported.…”
Section: Introductionmentioning
confidence: 88%
“…Another recent study indicated that the dysregulated of FN1 restricted prostate cancer cell invasion [12]. And the enhanced fibronectin expression in tamoxifen-resistant breast cancer cells had been reported by You et al [13]. However, the biological function of FN1 in RAIresistant PTC has few been reported.…”
Section: Introductionmentioning
confidence: 88%
“…Notably, the knockdown of UCA1 inhibits AKT phosphorylation in breast cancer cells (35). Additionally, activation of the PI3K/AKT signaling pathway has been demonstrated to confer resistance to antiestrogens in tamoxifen-resistant breast cancer cells (36). Therefore, it would be useful to determine whether UCA1 is involved in the PI3K/AKT signaling pathway and if it induces tamoxifen resistance in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not demonstrate a direct correlation between FN and p53 scores in the OCCCa/OHGSeCa category, indicating that a p53-independent pathway must regulate FN expression in the tumors, particularly in OCCCa. In fact, FN expression is upregulated through the PI3K/Akt pathway in tamoxifen-resistant breast cancer cells [51].…”
Section: Discussionmentioning
confidence: 99%